Newton's cradle: a metaphor to consider the flexibility, resistance and direction of nursing's future. Issue 2 (22nd May 2013) - McAllister, Margaret; Madsen, Wendy; Holmes, Colin
<x xml:space="preserve">Abstract</x> Nursing faces an uncertain future as technological developments, structural changes within health systems and rapidly evolving health needs create new and challenging possibilities. This article draws on the results of a qualitative study undertaken with a range of Queensland nurse leaders to explore their perceptions of these changes. The study re‐surfaced, and allows for a re‐examination of, four issues that have long created tension within nursing and which continue to have a negative impact on the profession as a whole. These are as follows: professionalisation; preparation of graduates; myths and narratives of nursing; and leadership. We provide a metaphor that imagines all of these tensions operating in dynamic interplay. The image is that of a Newton's Cradle – a model for energy and momentum. The metaphor allows one to see the wide context of changes affecting nursing and the significance of the interconnections. If tensions within nursing maintain their own integrity through containment, understanding and development, they remain in alignment, and energy is conserved rather than wasted or misdirected. It suggests that with increased awareness and attention paid to internal challenges, and by taking a broad‐based approach to systemic improvements, nursing could become more effective, progressive and proactive in shaping its own future.